2017
DOI: 10.20944/preprints201711.0199.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Self-Sampling for HPV Testing: Increased Cervical Cancer Screening Participation and Incorporation in International Screening Programs

Abstract: 26In most industrialized countries, screening programs for cervical cancer have 27 shifted from cytology (Pap smear or ThinPrep) alone on clinician-obtained samples to 28 the addition of screening for human papillomavirus (HPV), its main causative agent. For 29 HPV testing, self-sampling instead of clinician-sampling has proven to be equally 30 accurate, in particular for assays that use nucleic acid amplification techniques. In 31 addition, HPV testing of self-collected samples in combination with a follow-up… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…For our study, we used cervibroom, a standard brush used in gynecology clinics. There have been few other devices like solopap, dacronswabs, and digene conical collection used for this test as well . The cervibroom is already used for pap smears and comes at no extra cost; it is also easy to use.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For our study, we used cervibroom, a standard brush used in gynecology clinics. There have been few other devices like solopap, dacronswabs, and digene conical collection used for this test as well . The cervibroom is already used for pap smears and comes at no extra cost; it is also easy to use.…”
Section: Discussionmentioning
confidence: 99%
“…There have been few other devices like solopap, dacronswabs, and digene conical collection used for this test as well. 19,20,35,36 The cervibroom is already used for pap smears and comes at no extra cost; it is also easy to use. The most important difference is that with cervibroom-collected samples, a liquid-based cytology slide can be made if required.…”
Section: Digenous Women and Mortality Of Indigenous And Torres Straightmentioning
confidence: 99%
See 1 more Smart Citation
“…Human papillomavirus (HPV) testing has been reported to have high test performance, [11][12][13] and recent advancements in molecular techniques have led to the opportunity to use HPV testing as a screening method in low-income settings. 10 Previously, HPV testing required a gynecological examination; however, a vaginal sample can now be taken by the woman herself, which is referred to as HPV self-sampling or self-testing.…”
Section: Introductionmentioning
confidence: 99%
“…In these settings, HPV self-sampling has been reported to be well-accepted as it addresses many of the barriers that prevent women from attending screening. 12,14 Hence, it has the potential to increase cervical cancer screening uptake. However, studies have shown that some women are concerned about their ability to perform self-collection correctly or they are afraid of experiencing discomfort during the self-collection procedure.…”
Section: Introductionmentioning
confidence: 99%